The Impact of Flipped Classroom Strategy on Students’ English Language Learning Achievement of University Students - Saputra, Ari; Darmajaya, Lalu Arwan; Iswandi, Taufan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to investigate the effectiveness of the Flipped Classroom Strategy in improving students’ English language learning achievement at English department of FKIP Gunung Rinjani University. This research employs a quantitative approach with a quasi-experimental design involving two groups: an experimental group taught using the flipped classroom strategy and a control group taught using conventional methods. The participants of this study are students of English department of FKIP Gunung Rinjani University. Data are collected through pre-test and post-test to measure students’ English learning achievement. The data are analyzed using an independent sample t-test to determine the significance of differences between both groups. The expected findings of this study indicate that students taught through the flipped classroom strategy achieve significantly better results than those taught through traditional methods. In addition, the strategy is expected to improve students’ motivation, engagement, and independent learning skills. Therefore, this study is expected to contribute to the development of innovative English teaching strategies in higher education, particularly in improving students’ English language learning achievement.